Nutritional supplement practices of professional Ugandan athletes: a cross-sectional study - Haruna Muwonge; Robert Zavuga; Peninnah Aligawesa Kabenge; Timothy Makubuya (Taylor & Francis Group, 2017)
Background The use of nutritional supplements (NS) places athletes at great risk for inadvertent doping. Due to the paucity of data on supplement use, this study aimed to determine the proportion of Ugandan athletes using nutritional supplements and to investigate the athletes' motivation to use these supplements. Methods A cross-sectional study was conducted in which an interviewer-administered questionnaire was used to collect data from 359 professional athletes participating in individual (boxing, cycling, athletics) and team (basketball, rugby, football, netball, and volleyball) sports. The data were categorized, and a Chi-square test was used for statistical analysis. Results Of the 359 athletes, 48 (13.4%) used nutritional supplements. Carbohydrate supplements, energy drinks, vitamin and mineral supplements, fish oils, and protein supplements were the most common supplements used by athletes. NS use was significantly more common among athletes who played rugby and basketball (X 2 = 61.101, p < 0.0001), athletes who had played the sport for 5-10 years (X 2 = 7.460, p = 0.024), and athletes who had attained a tertiary education (X 2 = 33.377, p < 0.0001). The athletes' occupation had no bearing on whether they used supplements. Nutritionists/dieticians, retail stores and pharmacies were the most common sources of NS products, whereas health practitioners, online media and teammates were the most common sources of information regarding NS. Most athletes used NS to improve their physical performance and health. Conclusions Compared to NS use by athletes elsewhere, NS use among Ugandan athletes was low. However, determinants of athlete NS use in the current study (category of sport and duration of time spent playing the sport) are similar to those reported elsewhere.